TEACHING ENGLISH WITH DRAMA FOR YOUNG LEARNERS: SKILL OR CONFIDENCE? - G.M. Adhyanggono (Celt: A Journal of Culture, English Language Teaching & Literature, 2012)
There are various ways in teaching English to children. One of them is by using drama. Drama is basically an expressive activity that is, generally speaking, suitable for children's condition. The children's condition mentioned in this article deals a lot with their being dynamic, enthusiastic and full of imagination. The idea of using drama to support the learning process of children is increasingly recognised in a wide range of school settings. The children here are specifically aimed at students who are in pre and primary schools - young learners. Focusing on literacy and oracy processes, this article attempts to give an overview on how to use drama in teaching English for young learners.